2013
DOI: 10.1186/1471-2164-14-s3-s6
|View full text |Cite
|
Sign up to set email alerts
|

WS-SNPs&GO: a web server for predicting the deleterious effect of human protein variants using functional annotation

Abstract: BackgroundSNPs&GO is a method for the prediction of deleterious Single Amino acid Polymorphisms (SAPs) using protein functional annotation. In this work, we present the web server implementation of SNPs&GO (WS-SNPs&GO). The server is based on Support Vector Machines (SVM) and for a given protein, its input comprises: the sequence and/or its three-dimensional structure (when available), a set of target variations and its functional Gene Ontology (GO) terms. The output of the server provides, for each protein va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
221
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(222 citation statements)
references
References 39 publications
0
221
0
1
Order By: Relevance
“…The pathogenicity of the 23 missense mutations among the Arab population was assessed using five in silico prediction tools, namely, SNAP237 (https://www.rostlab.org/services/snap/), SIFT38 (http://sift.jcvi.org), PolyPhen-239 (http://genetics.bwh.harvard.edu/pph2/), SNPs&Go40 (http://snps-and-go.biocomp.unibo.it/snps-and-go/), and Mutationassessor41 (http://mutationassessor.org/). …”
Section: Methodsmentioning
confidence: 99%
“…The pathogenicity of the 23 missense mutations among the Arab population was assessed using five in silico prediction tools, namely, SNAP237 (https://www.rostlab.org/services/snap/), SIFT38 (http://sift.jcvi.org), PolyPhen-239 (http://genetics.bwh.harvard.edu/pph2/), SNPs&Go40 (http://snps-and-go.biocomp.unibo.it/snps-and-go/), and Mutationassessor41 (http://mutationassessor.org/). …”
Section: Methodsmentioning
confidence: 99%
“…Several recent articles have demonstrated this principle particularly well. For example, for SNPs&GO (Capriotti et al 2013b) the same learning procedure was followed with and without the additional Gene Ontology information (Ashburner et al 2000) to quantitate the improvement in prediction accuracy from this one additional data source. SNAP2 (Hecht et al 2015) reported results for multiple different machine-learning methods using the same set of features.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…However, he has a greater language and cognitive delay than usual, with only four words (all names) in his vocabulary at present. Table 1 In silico analyses of the LAMA2 gene * mutation Protein prediction programs PolyPhen-2 ** [6] Mutation taster [7] Mutation assessor [8] (functional impact) I-MUTANT 3.0 [9] PMut [10] MutPred [11] SNPs&GO [12] SIFT [13] Probably damaging The protein prediction programmes were queried using the above references, with the LAMA2 gene mutation formally described as c.7862G>T and p.Gly2621Val. ** Scores relate to predictions based on HumDiv and HumVar models.…”
Section: Discussionmentioning
confidence: 99%